2010
DOI: 10.1177/0261018310367676
|View full text |Cite
|
Sign up to set email alerts
|

‘Care Matters’ and the privatization of looked after children’s services in England and Wales: Developing a critique of independent ‘social work practices’

Abstract: The Children and Young Persons Act 2008 sets out parliamentary legislation that will allow local authorities in England and Wales to outsource their ‘corporate parenting’ function of social work services for children in public care to private or independent Social Work Practices (SWPs). The champions of private SWPs in the New Labour administration have found allies amongst the social work profession, including its professional body the British Association of Social Workers. This paper will briefly examine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…In particular, universities have become sites whereby one enhances one's 'human capital' in order to increase one's competitiveness in the global, flexible, jobs market, most evident through the employability agenda ubiquitous across campus life now [70]. Marketisation has also reached into spheres relevant to young people in the form of social work and child protection [71,72].…”
Section: Marketisationmentioning
confidence: 99%
“…In particular, universities have become sites whereby one enhances one's 'human capital' in order to increase one's competitiveness in the global, flexible, jobs market, most evident through the employability agenda ubiquitous across campus life now [70]. Marketisation has also reached into spheres relevant to young people in the form of social work and child protection [71,72].…”
Section: Marketisationmentioning
confidence: 99%
“…However, these powers appear to have fallen into disuse (NSPCC, personal communication). The introduction of SWPs was depicted as an attempt to bring quasi-markets into welfare and was described by critics as the privatisation of children's welfare services and the commodification of children (Cardy, 2010;Garrett, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In this, he drew on the arguments of researchers such as Stein (2006) and Forrester et al (2009) who have emphasised the heterogeneity of children's experiences in the looked after system and who maintain that outcomes for looked after children reflect the needs that bring them into care. Second, Garrett claimed that SWPs were introduced without meaningful consultation of looked after children or their parents Other critics have suggested that SWPs will be required to meet the same bureaucratic demands as local authority children's services, particularly in relation to the much criticised electronic records system, the Integrated Children's System (Cardy, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past 8 years children's social work services have been increasingly opened up to the market place This was seen at the time as a start of positioning for privatisation statutory social work services for children (Garrett, 2008;Cardy, 2010), and it has been commented that:…”
Section: A Brief Resume Of the Recent Children's Social Work And Chilmentioning
confidence: 99%